2021
DOI: 10.22515/al-balagh.v6i2.3501
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the “Digital Prank” Phenomenon From the Psychology Perspective

Abstract: This study aims at understanding the motivations and emotions of prank proprietors. The prank phenomenon that is now gaining popularity in society is seen as something that causes material losses such as money and goods as well as immaterial such as trauma and distrust. The informan of this study are 3 (three) YouTubers who have created prank content and uploaded it to YouTube (prank proprietors). This research was conducted in DKI Jakarta and Central Java. The data were collected through a phenomenological ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Imron Rosyidi revealed that YouTubers create prank content for reasons of entertainment, fun and to make money. The reason for earning money is very logical because this research shows that prank content tends to be liked by netizens or viewers (Haq & Rosyidi, 2021). The perception of the type of prank doesn't matter.…”
Section: Social Contextmentioning
confidence: 94%
“…Imron Rosyidi revealed that YouTubers create prank content for reasons of entertainment, fun and to make money. The reason for earning money is very logical because this research shows that prank content tends to be liked by netizens or viewers (Haq & Rosyidi, 2021). The perception of the type of prank doesn't matter.…”
Section: Social Contextmentioning
confidence: 94%
“…There are incidents in which, in the name of playing pranks, people are crossing the line, invading other people's privacy, and sometimes infringing on their fundamental human rights. Haq and Rosyidi (2021) observed that the most disturbing aspect of pranks is that they impair society's ability to distinguish between actual and phony events. It is against this backdrop that this paper seeks to examine the social implications of pranks in Nigerian society.…”
mentioning
confidence: 99%